Wartości w świecie dziecka w przekonaniach dorosłych – przyszłych nauczycieli - Marzenna Nowicka (Problemy Wczesnej Edukacji)
Educational practice is directly connected with how and what teachers think about the students. In the text are presented the results of researches into common beliefs of students from teaching faculties concerning values in the children’s world. Analyses show worrying tendencies in the way of thinking of future teachers about the students: they perceive them as being passive, very dependent on adults, concentrated on themselves, potentially more prone to harm rather than to good. In the understanding of students, children learn bad values from pathological adults, peers, and the media.